GIT1 protects against breast cancer growth through negative regulation of Notch - Zhang Songbai; Miyakawa Ayako; Wickström Malin; Dyberg Cecilia; Louhivuori Lauri; Varas-Godoy Manuel; Kemppainen Kati; Kanatani Shigeaki; Kaczynska Dagmara; Ellström Ivar Dehnisch; Elfman Lotta; Kronqvist Pauliina; et al. (NATURE PORTFOLIO, 2022)
Notch signalling is reported to be hyperactivated in oestrogen receptor-negative (ER-) breast cancer. Here the authors show that G protein-coupled receptor kinase-interacting protein 1 (GIT1) negatively regulates Notch signalling and tumour growth in ER- breast cancer by blocking Notch ICD nuclear translocation.Hyperactive Notch signalling is frequently observed in breast cancer and correlates with poor prognosis. However, relatively few mutations in the core Notch signalling pathway have been identified in breast cancer, suggesting that as yet unknown mechanisms increase Notch activity. Here we show that increased expression levels of GIT1 correlate with high relapse-free survival in oestrogen receptor-negative (ER(-)) breast cancer patients and that GIT1 mediates negative regulation of Notch. GIT1 knockdown in ER(-) breast tumour cells increased signalling downstream of Notch and activity of aldehyde dehydrogenase, a predictor of poor clinical outcome. GIT1 interacts with the Notch intracellular domain (ICD) and influences signalling by inhibiting the cytoplasm-to-nucleus transport of the Notch ICD. In xenograft experiments, overexpression of GIT1 in ER(-) cells prevented or reduced Notch-driven tumour formation. These results identify GIT1 as a modulator of Notch signalling and a guardian against breast cancer growth.